2014
DOI: 10.1007/s00376-013-3152-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meridional sea surface temperature changes on stratospheric temperature and circulation

Abstract: Article:Hu, D, Tian, W, Xie, F et al. (2 more authors) (2014) Effects of meridional sea surface temperature changes on stratospheric temperature and circulation. Advances in Atmospheric Sciences, 31 (4). 888 -900. ISSN 0256-1530 https://doi.org/10.1007/s00376-013-3152-6 eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 44 publications
(47 reference statements)
4
58
1
3
Order By: Relevance
“…It is noteworthy that warm (cold) SST anomalies are generally thought to increase (suppress) planetary wave activity via strengthening (weakening) convection (Xie et al, 2008;Shu et al, 2011;Hu et al, 2014). However, this study shows that warm (cold) SST anomalies over the marginal seas of East Asia suppress (increase) planetary wave activity in the southern high-latitude stratosphere.…”
Section: S3contrasting
confidence: 43%
“…It is noteworthy that warm (cold) SST anomalies are generally thought to increase (suppress) planetary wave activity via strengthening (weakening) convection (Xie et al, 2008;Shu et al, 2011;Hu et al, 2014). However, this study shows that warm (cold) SST anomalies over the marginal seas of East Asia suppress (increase) planetary wave activity in the southern high-latitude stratosphere.…”
Section: S3contrasting
confidence: 43%
“…Previous studies have shown that an increase in GHGs leads to a warmer troposphere and a cooler stratosphere via its direct radiational effects and indirect SST effects, which in turn affects the wave propagation from the troposphere into the stratosphere and further strengthens the BDC [5]. Stratospheric ozone has important impacts on the BDC Advances in Meteorology through the radiational and chemical processes [2,45,46].…”
Section: Effects Of Ghgs and The Stratospheric Ozone On The Bdcmentioning
confidence: 99%
“…During 2001-2050, the warmed Antarctic stratosphere may lead to a weakened latitudinal temperature gradient ( Figure 6(c)), which, following the thermal wind relationship, would be accompanied by a weakened westerly wind in the Antarctic stratosphere and an equatorward displacement of the southern subtropical jet (Figure 6(d)). The above-mentioned zonal wind changes imply a change in refractive index [10], which in turn can influence the propagation of planetary waves from the troposphere to the stratosphere [5,43]. As the eddy heat flux (V ) can well represent the vertical flux of wave activity well [44], we examine the trends of eddy heat flux in DJF during the two periods (Figure 7).…”
Section: Planetary-wave Flux Trendsmentioning
confidence: 99%
See 2 more Smart Citations